Agile risk management for multi‐cloud software development. Issue 3 (1st June 2019) - Muntés-Mulero, Victor; Ripolles, Oscar; Gupta, Smrati; Dominiak, Jacek; Willeke, Eric; Matthews, Peter; Somosköi, Balázs
Abstract : Industry in all sectors is experiencing a profound digital transformation that puts software at the core of their businesses. To react to continuously changing user requirements and dynamic markets, companies need to build robust workflows that allow them to increase their agility in order to remain competitive. This increasingly rapid transformation, especially in domains such as Internet of things or cloud computing, poses significant challenges to guarantee high‐quality software, since dynamism and agile short‐term planning reduce the ability to detect and manage risks. In this study, the authors describe the main challenges related to managing risk in agile software development, building on the experience of more than 20 agile coaches operating continuously for 15 years with hundreds of teams in industries in all sectors. They also propose a framework to manage risks that consider those challenges and supports collaboration, agility, and continuous development. An implementation of that framework is then described in a tool that handles risks and mitigation actions associated with the development of multi‐cloud applications. The methodology and the tool have been validated by a team of evaluators that were asked to consider its use in developing an urban smart mobility service and an airline flight scheduling system.